2008
DOI: 10.1556/achrom.20.2008.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a densitometric TLC method for analysis of trigonelline and 4-hydroxyisoleucine in fenugreek seeds

Abstract: A simple, sensitive, and reproducible high-performance thin-layer chromatographic method has been established for simultaneous analysis of trigonelline and 4hydroxyisoleucine from fenugreek seeds (Trigonella foenum-graceum). Chromatography was performed on silica gel GF 254 with n-butanol-methanol-acetic acid-water 4:1.5:1:1 (v/v) as mobile phase. Densitometric scanning of the plates at 266 nm was used for analysis of trigonelline, and plates were scanned at 395 nm after derivatisation with ninhydrin reagent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…There are numerous other uses of fenugreek, including treatment of indigestion and baldness. [1,2] Seeds are known for their pungent aromatic properties. [3] The seeds, available in whole and ground forms, are used to flavour many foods including curry powders, spice blends and teas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous other uses of fenugreek, including treatment of indigestion and baldness. [1,2] Seeds are known for their pungent aromatic properties. [3] The seeds, available in whole and ground forms, are used to flavour many foods including curry powders, spice blends and teas.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The literature search showed that few analytical methods have been published for fenugreek such as high performance thin layer chromatography (HPTLC) determination of trigonelline and 4-hydroxyisoleucine from fenugreek seed. [2] But Comparison between high performance liquid chromatography and high performance thin layer chromatography determination of Diosgenin from fenugreek seeds there is no analytical method available for the estimation of Diosgenin from fenugreek seeds.…”
Section: Introductionmentioning
confidence: 99%
“…In China, it is a medicinal and edible plant for making pancakes, and its seeds are included in the ''Chinese Pharmacopoeia''. Saponins [1], flavonoids [2,3], galactomannans [4], trigonelline, and 4-hydroxyisoleucine [5] were isolated from fenugreek seeds in previous phytochemical research studies. The seeds are used in folk medicine because of their reported hypoglycemic [6], hypolipidemic, antidiabetic [7], liver-protective [8], renoprotective, anticancer [9], and antioxidant [10] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological activities such as antiinflammatory [4], antimicrobial [5], neuromuscular [6], and toxicity studies [7] are reported on leaves. It is also a major ingredient of many marketed polyhedral digestive mixtures such as Chatak ® . Leaves are foremost source of an alkaloid trigonelline [8] having diverse pharmacological activities such as hypoglycemic, hypocholesterolemic, antiseptic, antimigraine, antitumor, mutagenic, and osmoregulatory [9]. Hence, active principle trigonelline has been used as a marker compound for quality control and standardization of the A. precatorius leaves and its formulations.…”
Section: Introductionmentioning
confidence: 99%